Comparing the effect of using 2-Mercaptoethanol in the cell culture medium of different cell passages of human mesenchymal stem cells: 2-Mercaptoethanol use in the mesenchymal stem cells culture medium - Khasawneh, Ramada R.; Abu-El-Rub, Ejlal (Cellular and Molecular Biology, 2024)
Preparing a suitable cell culture medium that supports the biological needs of the growing cells is crucial to enhancing the success rate of any in vitro and in vivo experiments and minimizing undesirable interferences. Mesenchymal stem cells ( MSCs) which are powerful regenerative stem cells require being grown in proper culture media to preserve their stemness and therapeutic properties. MSCs are usually grown in Dulbecco's Modified Eagle low glucose Medium (DMEM low glucose) which contains 5.6 mmol/L of glucose and is supplemented with Fetal Bovine Serum (FBS), antibiotics, and 2-Mercaptoethanol. The addition of 2-Mercaptoethanol to the cell culture medium was proposed long ago and has continued to be used until now. Despite the positive effects of adding 2-Mercaptoethanol in the cell culture medium, its use is still controversial and needs continuous updates to limit its interference with experimental treatments. Herein, we found that 2-Mercaptoethanol is beneficial to enhancing the proliferation and survival of MSCs at higher passage numbers while its effect is negligible for earlier passages. This concise study provides updates regarding the suitable time to add 2-Mercaptoethanol which can minimize its intermeddling with the experimental design and treatments.